2019
DOI: 10.1038/s41398-019-0402-0
|View full text |Cite
|
Sign up to set email alerts
|

Genome-wide association scan identifies new variants associated with a cognitive predictor of dyslexia

Abstract: Developmental dyslexia (DD) is one of the most prevalent learning disorders, with high impact on school and psychosocial development and high comorbidity with conditions like attention-deficit hyperactivity disorder (ADHD), depression, and anxiety. DD is characterized by deficits in different cognitive skills, including word reading, spelling, rapid naming, and phonology. To investigate the genetic basis of DD, we conducted a genome-wide association study (GWAS) of these skills within one of the largest studie… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
105
3

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 93 publications
(113 citation statements)
references
References 116 publications
5
105
3
Order By: Relevance
“…The datasets involved in the present study were collected in nine different populations of European ancestry, with six different languages (see Table 1). Subsets have already been tested for association with continuous reading-related traits [28]. Ethical approval was obtained for each cohort at the local level, and written informed consent was obtained for all the participants or their parents.…”
Section: Datasetsmentioning
confidence: 99%
See 4 more Smart Citations
“…The datasets involved in the present study were collected in nine different populations of European ancestry, with six different languages (see Table 1). Subsets have already been tested for association with continuous reading-related traits [28]. Ethical approval was obtained for each cohort at the local level, and written informed consent was obtained for all the participants or their parents.…”
Section: Datasetsmentioning
confidence: 99%
“…DD and readingrelated cognitive traits have also been investigated via genome-wide association studies (GWAS), which involve analyses of many single-nucleotide polymorphisms (SNPs) spread across the genome. A few such studies have been reported, using either a case-control design [23][24][25] or a continuous trait analysis approach [26][27][28][29][30]. However, only two of these studies identified associations that met criteria for genome-wide significance [27,28].…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations